Immobilization and stabilization of d-hydantoinase from Vigna angularis and its use in the production of N-carbamoyl-d-phenylglycine. Improvement of the reaction yield by allowing chemical racemization of the substrate. (August 2020) - Becaro, Aline Aparecida; Mendes, Adriano Aguiar; Adriano, Wellington Sabino; Lopes, Laiane Antunes; Vanzolini, Kenia Lourenço; Fernandez-Lafuente, Roberto; Tardioli, Paulo Waldir; Cass, Quezia Bezerra; Giordano, Raquel de Lima Camargo
Graphical abstract: Highlights: D-hydantoinase immobilized on glyoxyl agarose presented ca.60 % recovered activity. Presence of Zn +2 in the active site was necessary to maintain the catalytic activity. Immobilized d -hydantoinase was 86-fold more stable than the free enzyme. d, l -phenylhydantoin was efficiently hydrolyzed to N -carbamoyl-d -phenylglycine. High enantioselectivity (>99 %) was achieved under substrate racemization conditions. Abstract: This work reports the immobilization of a multimeric d -hydantoinase (DHTase) from Vigna angularis (E.C. 3.5.2.2.) on agarose beads activated with glyoxyl groups aiming to improve its stability via multipoint covalent attachment. The final reduction with sodium borohydride resulted in a drop in enzyme activity that could be decreased by adding Zn 2+ or Mg 2+ . The optimal preparation with high activity (58 % recovered activity) and stability (around 86-fold more stable than the free enzyme) was obtained by DHTase immobilization on glyoxyl agarose for 24 h at 25 °C and pH 10.05, and a borohydride reduction step in the presence of 10 mM Zn 2+ (DHTase-Glx). The enzyme was almost fully immobilized on glyoxyl agarose (19.8 mg/g of support) when offering 20 mg/g. This immobilized biocatalyst was used to catalyze the hydrolysis of d, l -phenylhydantoin under substrate racemization conditions, which produced 99 % of N-carbamoyl-d -phenylglycine after 9 h reaction.